Implementación de un sistema de control y administración de procesos aplicando la metodología extreme programming para el colegio Catorce de Julio ubicado en la parroquia san Buenaventura del cantón Latacunga, provincia de Cotopaxi, durante el año 2013 - Chimba Pilatasig, Pedro Omar (2015)
This research refers the implementation of a system of control and management process for the “Catorce de Julio” high school in Latacunga City. The proposal was made with porpose to satisfy the necessities of the institution, as it was evident that the registration of notes, the reports and information of the students are taken in an ofimatic system and files. The system contains differents modules that allows: the inscription and registration of students’ assignment of parallels, subject matters’ and teachers’ for every course, users can also consult: notes, payroll, and information of the institution. All these processes was stored in a database thus providing security to the information generated by them. For the elaboration of the proposal, the methodology Agile XP (Extreme Programming) was applied which helped with phases to planning and analyze its content, to design and to realize out several tests of the application for the correct development of the investigation....